The Legal Certainty of Electronic Land Certificates in Land Law in Indonesia - Hadi, Nofa Isnan (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
The aims of this study were to analyze: 1) Legal certainty of electronic land title certificates in Indonesian land registration law 2). Obstacles and solutions in the implementation of making electronic-based land certificates in Indonesia. The approach method used in this study is a normative juridical approach. The specification of the research used is descriptive analytical research. This type of data uses secondary data sourced from literature. The data analysis method used in this research is qualitative data analysis. The results of the study concluded: 1). The legal certainty of electronic land title certificates in the law of land registration in Indonesia is the urgency of holding land registration. The ultimate goal of the land registration process is the issuance of a document proving the right to land ownership, which is then referred to as a certificate. Electronic land certificates as proof of electronic ownership recognized by the ITE Law, especially those stipulated in Article 6. In terms of validity and legal certainty, there is no problem, let alone it has also been strengthened in Article 5 of the ATR/BPN Ministerial Regulation Number 1 of 2021. Legal certainty of electronic certificates in Electronic document forms can be categorized as electronic evidence which has the same evidentiary power as written/written evidence made on paper and printed results as a valid form of evidence. This is a reference to the legitimacy of the position of the electronic certificate to be used as evidence in court as long as the data stored in the electronic system does not change (guaranteed its integrity) according to what is in the land book. 2). Obstacles in implementing electronic-based land certificates in Indonesia are the incomplete land database, there are still population problems such as E-KTP, the existence of laws and regulations that are still not in sync, limited internet access to access electronic certificates, lack of socialization of electronic certificates from the Government. The solution that can be done is to synchronize and complete the land database, solve population problems.Keywords: Certainty; Certificate, Land; Registration.